Hidden Anchor: A Lightweight Approach for Physical Layer Location Privacy - El-Badry, Rania; Youssef, Moustafa; Sultan, Ahmed (Journal of Computer Systems, Networks, and Communications, 2010)
In hybrid wireless sensor networks, where trusted and un-trusted nodes coexist, itbecomes important to allow trusted nodes to share information, especially, locationinformation and prevent un-trusted nodes from gaining access to this information. We focus on anchor-based localization algorithms in WSNs, where a small set ofspecialized nodes, that is, anchor nodes, broadcast their location to the network andother nodes can use the broadcast information to estimate their own location. Themain challenge is that both trusted and un-trusted nodes can measure the physicalsignal transmitted from anchor nodes and use it to estimate their locations. In thispaper, we propose Hidden Anchor, an algorithm that provides anchor physicallayer location privacy for different classes of localization algorithms. The HiddenAnchor algorithm exploits the inherently noisy wireless channel and uses identitycloning of neighboring trusted nodes to make anchors unobservable to un-trustednodes while providing complete information to trusted nodes. Evaluation of theHidden Anchor algorithm through analysis and simulation shows that it can hidethe identity, and hence the location, of anchor nodes with very low overhead. Inaddition, the results show that by adding artificial noise, we can achieve significantimprovement in anchor's location privacy.